Communication management 2.0: The development of three socio-cognitive models for brand page usage. Issue 2 (2nd May 2017) - Ruehl, Christopher Hendrik; Ingenhoff, Diana
Abstract : Purpose: The purpose of this paper is to investigate how and why individuals use corporate pages on Facebook with the aim of developing a usage-specific inventory of incentive factors which describe brand page utilization for consumption, participation and production behavior. Design/methodology/approach: A combined perspective of uses-and-gratifications (U&G) and social cognitive theory (SCT) was applied to develop three models of brand page behavior. Based on a literature review, an online survey ( N =215) was conducted. Exploratory factor analyses identified motivational factors based on SCT incentive dimensions, which were cross-validated using confirmatory factor analysis (CFA). Findings: Results indicate that consumption behavior can best be explained by activity, self-reactive-novel and monetary incentives. Status incentives, practical-novel and self-reactive-idealistic incentives drive participation. Production behavior is best explained by social, self-reactive and status incentives. Practical implications: The models' strategic implications for integrated communication management are discussed. Originality/value: The results suggest interconnections of incentive dimensions unique to brand page usage, which have not yet been explored in any research.